IOT based industrial load control and safety management - Hasan, Md. Mehedi; Islam, Shah Rukh; Mohammad, Yousuf (Brac University, 2024)
This final year design project is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2022.